Evaluation of flexible floating anti-collision device subjected to ship impact using finite-element method. (15th April 2019) - Wang, J.J.; Song, Y.C.; Wang, W.; Chen, C.J.
Abstract: Ship impact is a potential hazard for bridge piers located in navigation waterways. To avoid direct contact between the ship and the pier, protective structures of different types are currently widely used in bridge designs against ship impact. As one of these protective structures, the flexible floating device has drawn much attention in recent years. The main advantage of this device lies in its low cost and its ability to float on water surface regardless of water elevation. This paper aims to evaluate the effectiveness of a flexible floating anti-collision device adopted in the Zhanjiang Bay Bridge located in Guangdong Province, China, using finite-element models. Detailed illustrations of the structural configurations are provided. In addition, finite-element models of the ship and the floating device with calibrations using experimental data are developed. The influences of several factors upon the ability of the device to turn the navigation direction of the ship, the energy-dissipation capacity of the device and the effectiveness of the device for reducing the impact force on the pier, are thoroughly evaluated using the validated finite-element models.